2021
DOI: 10.3390/plants10102177
|View full text |Cite
|
Sign up to set email alerts
|

Proline-Mediated Drought Tolerance in the Barley (Hordeum vulgare L.) Isogenic Line Is Associated with Lateral Root Growth at the Early Seedling Stage

Abstract: A vigorous root system in barley promotes water uptake from the soil under water-limited conditions. We investigated three spring barley genotypes with varying water stress responses using rhizoboxes at the seedling stage. The genotypes comprised two elite German cultivars, Barke and Scarlett, and a near-isogenic line, NIL 143. The isogenic line harbors the wild allele pyrroline-5-carboxylate synthase1-P5cs1. Root growth in rhizoboxes under reduced water availability conditions caused a significant reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…Moreover, the barley near-isogenic line NIL 143 , characterized by higher leaf and root proline content, showed less severe symptoms of drought, higher leaf water content, better stomatal conductance and net CO 2 assimilation than other genotypes. This barley line also exhibited increased lateral root growth, probably due to high proline accumulation [ 103 ]. Considerable evidence obtained previously revealed that drought-stress-induced expression of proline biosynthetic genes is regulated by TFs related to almost all plant hormones [ 67 ].…”
Section: Drought Coping Strategies and Resistancementioning
confidence: 99%
“…Moreover, the barley near-isogenic line NIL 143 , characterized by higher leaf and root proline content, showed less severe symptoms of drought, higher leaf water content, better stomatal conductance and net CO 2 assimilation than other genotypes. This barley line also exhibited increased lateral root growth, probably due to high proline accumulation [ 103 ]. Considerable evidence obtained previously revealed that drought-stress-induced expression of proline biosynthetic genes is regulated by TFs related to almost all plant hormones [ 67 ].…”
Section: Drought Coping Strategies and Resistancementioning
confidence: 99%
“…Under field conditions, Scarlett accumulated 24% lower proline in the leaves compared to NIL-143 (Supporting Information: Figure S9). In addition, QPro.S42-1H ILs accumulated more proline in the spikes, and the spike abortion was significantly reduced under drought stress (Frimpong, Windt, et al, 2021). In the present study, the drought stress-induced reduction in yield attributing traits such as grain numbers per ear, grain weight per plant, harvest index, and thousand-grain weight, in particular, were higher in Scarlett compared with NIL-143 (Figure 7a,b and Supporting Information:…”
Section: Discussionmentioning
confidence: 50%
“…However, it has also been shown that proline accumulation in the leaf and the partitioning to other organs and turnover of proline are essential for proline‐mediated drought tolerance (Sharma et al, 2011). In a previous study, we demonstrated that the NIL‐143 accumulates higher proline in the roots than Scarlett (Frimpong, Anokye, et al, 2021), indicating the efficient partitioning of proline from the source (leaf) to the sink (root). Therefore, NIL‐143 is an excellent genetic material for exploring the mechanistic process of proline‐mediated osmoregulation, redox balance, photosynthetic adjustments, and cellular signaling during drought stress.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In general, tolerant genotypes of crop plants accumulated more osmoprotectants with high concentrations than sensitive genotypes under stress. For example, a near-isogenic line of spring barley genotypes (NIL143) that contains the wild allele pyrroline-5-carboxylate synthase 1-P5cs1 was observed higher proline concentrations in leaf and root and less severe symptoms of drought compared with any other genotypes under reduced water availability conditions (Frimpong et al, 2021).…”
Section: Proline Levels Increased In the Ga2 Millet Variety Under Atr...mentioning
confidence: 99%